Added Value of Cognition in the Prediction of Survival in Low and High Grade Glioma - van Kessel, Emma; Schuit, Ewoud; Huenges Wajer, Irene M. C.; Ruis, Carla; De Vos, Filip Y. F. L.; Verhoeff, Joost J. C.; Seute, Tatjana; van Zandvoort, Martine J. E.; Robe, Pierre A.; Snijders, Tom J. (Frontiers in Neurology, 2021)
Background: Diffuse gliomas, which are at WHO grade II-IV, are progressive primary brain tumors with great variability in prognosis. Our aim was to investigate whether pre-operative cognitive functioning is of added value in survival prediction in these patients. Methods: In a retrospective cohort study of patients undergoing awake craniotomy between 2010 and 2019 we performed pre-operative neuropsychological assessments in five cognitive domains. Their added prognostic value on top of known prognostic factors was assessed in two patient groups [low- (LGG) and high-grade gliomas (HGG]). We compared Cox proportional hazards regression models with and without the cognitive domain by means of loglikelihood ratios tests (LRT), discriminative performance measures (by AUC), and risk classification [by Integrated Discrimination Index (IDI)]. Results: We included 109 LGG and 145 HGG patients with a median survival time of 1,490 and 511 days, respectively. The domain memory had a significant added prognostic value in HGG as indicated by an LRT (p-value = 0.018). The cumulative AUC for HGG with memory included was.78 (SD = 0.017) and without cognition 0.77 (SD = 0.018), IDI was 0.043 (0.000–0.102). In LGG none of the cognitive domains added prognostic value. Conclusions: Our findings indicated that memory deficits, which were revealed with the neuropsychological examination, were of additional prognostic value in HGG to other well-known predictors of survival.